2003
DOI: 10.1161/01.str.0000090351.41662.91
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study of Single and Multiple Lacunar Infarcts Using Magnetic Resonance Imaging

Abstract: Background and Purpose-We investigated whether lacunar infarct (LI) patients with Ͼ1 lacune have different vascular risk factors, a different prognosis, and poorer functional outcome than those with a single lacune. Methods-The study included 175 first-ever LI patients. The group was divided according to the presence of multiple (nϭ136)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
62
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(69 citation statements)
references
References 60 publications
6
62
0
1
Order By: Relevance
“…Although never-symptomatic carotid artery occlusions were reported to carry a very low risk of subsequent ischemic stroke due to a low incidence of increased oxygen extraction fraction (35), it is well known that large-artery arteriosclerosis confers an increased risk of stroke recurrence (36). In fact, stroke recurrence is greater in patients with multiple lacunar infarcts compared to those with only one lacunar infarct (37). This corresponds to the clinical observation that patients who have suffered a TIA have a high risk of subsequent stroke, death, or disability (38).…”
Section: Discussionmentioning
confidence: 99%
“…Although never-symptomatic carotid artery occlusions were reported to carry a very low risk of subsequent ischemic stroke due to a low incidence of increased oxygen extraction fraction (35), it is well known that large-artery arteriosclerosis confers an increased risk of stroke recurrence (36). In fact, stroke recurrence is greater in patients with multiple lacunar infarcts compared to those with only one lacunar infarct (37). This corresponds to the clinical observation that patients who have suffered a TIA have a high risk of subsequent stroke, death, or disability (38).…”
Section: Discussionmentioning
confidence: 99%
“…Of the 12 studies categorized as "vascular cohorts," 1 showed a significant association between diabetes and silent lacunar infarcts (27) and 4 between diabetes and symptomatic lacunar infarcts (28 -31). Of the four studies categorized as "outpatient cohorts," one showed a significant association between diabetes and silent lacunar infarcts (22).…”
Section: Van Harten and Associatesmentioning
confidence: 99%
“…They are typically characterised by a regular shape that is frequently rounded or tube-like with a diameter of 0.2 -2 cm [11][12][13]. SSI account for up to 25% of all strokes [14] and occur predominantly in patients with small vessel disease, such as diabetes and hypertension [10].…”
Section: Introductionmentioning
confidence: 99%
“…There have been only a few MRI studies of small subcortical infarcts [14,[16][17][18][19][20][21][22][23][24]. Only smaller than the DWI lesion [21].…”
Section: Introductionmentioning
confidence: 99%